Seismic-wave path attenuation and local site responses in eastern Guangdong province revealed by the ground-motion spectral analyses - Wu, Huadeng; Zhou, Ying; Qian, Yongmei; Yang, Fang; Yu, Gang; Wu, Guorui; Zhang, Yi (Frontiers in Earth Science, 2023)
In an effort to investigate the attenuation characteristics and site effects in eastern Guangdong, 659 strong-motion recordings received by 27 stations were selected for spectral analysis to separate path attenuation, site effects and source spectra. The path attenuation curves are generally close to the simplest form of distance decay described by R-0.5, and decays the slowest at a frequency of 4 Hz. We decomposed the path attenuation into a combination of geometric spreading and inelastic attenuation. The geometric spreading R-0.15 exhibits a slower distance decay at local distances, indicating that the seismic energy close to the epicenter is not easily dissipated. The quality factors were regressed as Qs(f) = 114.81f 0.922 in the frequency range 0.9-20 Hz, lower than those reported for the whole Guangdong region, indicating stronger anelastic attenuation in eastern Guangdong. The site responses in eastern Guangdong show a strong correlation with geological and geotechnical characterization. The stations located in the central mountains have higher predominant frequencies (>10 Hz) accompanied by smaller site amplifications. Larger site amplification is in the southeast coastal area (i.e. Shantou area), where the surface is covered with a thicker layer of soft soil and the predominant frequency of site is relatively low (~2 Hz). The far-field earthquake will cause greater vibration and damage to this area.